Understanding Microelectronics : a Top-Down Approach. - Maloberti, Franco (John Wiley & Sons, 2011)
The microelectronics evolution has given rise to many modern benefits but has also changed design methods and attitudes to learning. Technology advancements shifted focus from simple circuits to complex systems with major attention to high-level descriptions. The design methods moved from a bottom-up to a top-down approach. For today's students, the most beneficial approach to learning is this top-down method that demonstrates a global view of electronics before going into specifics. Franco Maloberti uses this approach to explain the fundamentals of electronics, such as processing functions, si.